(3GdHdZI aj JaSjQ GdbQBf GdcQjes - (3GdYHGS eMeO Hf eMeO Hf CMeO GdMce GdWhSjs
(3ChdgG (B:s
(3JaSjQ ShQI eQje s
(3BNQgG (B:s
(3jfJgi HBNQ JaSjQ ShQI U s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG ebGHdGJs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ GdZQHjI (B((3JaSjQ (B21) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs